A four-primary-color micro-LED display with wide color gamut, low blue light hazard, and promise to improve working efficiency in the working conditions - Peiyu Sun; Min Min; Qingfeng Wu; Weijun Huang; Qing Xiao; Wei Xiao; Chaodan Zheng (AIP Advances)
Attention should be paid to the circadian rhythm effect, photobiological safety, and color gamut coverage (CGC) of displays. In this study, we use genetic algorithm to search the displays satisfying the demands of health, wide color gamut, and promise to improve working efficiency in the working conditions, when the correlated color temperature is around 6500 K. We also studied the variations in optimal results when changing the peak wavelength and full width at half maximum (FWHM), finding that the impacts of peak wavelengths are greater than those of FWHMs on the circadian action factor (CAF), blue light hazard, and CGC, and a balance should be made between the CAF and the luminous efficacy of radiation.